2017
DOI: 10.1002/ijfe.1576
|View full text |Cite
|
Sign up to set email alerts
|

Eurozone cycles: An analysis of phase synchronization

Abstract: This paper analyses synchronization, both across and between business and financial cycles (growth and classical) in a subset of 10 countries representative of the Economic and Monetary Union. Employing an extended data set from 1960 to 2013, we find evidence of synchronization across financial cycles. In case of business cycles, we find contrasting results: There is significant synchronization across growth cycles but no evidence of a common classical cycle. This confirms, first, that economic and financial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Equity prices (see, e.g . Claessens et al ., ; Granville and Hussain, ), bond prices (Schüler et al ., ), interest rates, non‐performing loans, volatilities, risk premia and the credit‐to‐GDP ratio (Borio, 2014b) have all been used.…”
Section: Definitions and Data Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equity prices (see, e.g . Claessens et al ., ; Granville and Hussain, ), bond prices (Schüler et al ., ), interest rates, non‐performing loans, volatilities, risk premia and the credit‐to‐GDP ratio (Borio, 2014b) have all been used.…”
Section: Definitions and Data Transformationsmentioning
confidence: 99%
“…(), Drehmann et al . () and Granville and Hussain () provide turning point analyses. The approach has been employed in the South African context by Du Plessis () for the business cycle, and Boshoff () for financial variables.…”
Section: Approaches To Measurementmentioning
confidence: 99%
“…Similar analyses have been made by various scholars. sectional regression model and Granville (2017) analysed European countries' business cycles over the period 1961–2013 and found that, most recently, the concordance index is 0.67 for the 1993–2002 period, 0.75 for 2003–2008, and 0.96 for 2009–2013. Similarly, focusing on concordance among US states, Duran (2014) found it to be 0.73 for 1993–2008, and Owyang et al (2005) found it to be 0.8 for the period 1979–2002.…”
Section: Asymmetries In Italian Regional Business Cyclesmentioning
confidence: 99%
“…Equity prices (see, e.g. Claessens et al, 2011;Granville and Hussain, 2017), bond prices (Schüler et al, 2015), interest rates, non-performing loans, volatilities, risk premia and the credit-to-GDP ratio (Borio, 2014b) have all been used. 6 We opt for a parsimonious specification that includes credit, property prices and equity prices in this initial analysis of the South African financial cycle, although it is accepted that further research into this issue is warranted.…”
Section: Definitions and Data Transformationsmentioning
confidence: 99%
“…Following Burns and Mitchell (1946), traditional turning-point analysis defines the cycle as a pattern in the level of economic activity. In the financial cycle literature, Claessens et al (2011Claessens et al ( , 2012, Drehmann et al (2012) and Granville and Hussain (2017) provide turning point analyses. The approach has been employed in the South African context by Du Plessis (2006) for the business cycle, and Boshoff (2005) for financial variables.…”
Section: Turning-point Analysismentioning
confidence: 99%